Neurotoxic effects of different sizes of plastics (nano, micro, and macro) on juvenile common carp (Cyprinus carpio) - Hamed, Mohamed; Martyniuk, Christopher J.; Naguib, Mervat; Lee, Jae-Seong; Sayed, Alaa El-Din H. (Frontiers in Molecular Neuroscience, 2022)
Using common carp as a model, we assessed the effects of polyethylene (PE) plastics on the brain. We measured activity of acetylcholinesterase (AChE), monoamine oxidase (MAO), and the content of nitric oxide (NO) in carp brain following exposure to 100 mg/L of either macroplastics (MaP), microplastics (MPs), or nanoplastic (NPs) for 15 days compared to an unexposed group. Following exposure, each biochemical biomarker was reduced 30–40%, with a higher magnitude of change corresponding to the smaller size of the particles (NPs > MPs > MaPs). In the carp tectum, exposure for 15 days to plastic particles caused varying degrees of necrosis, fibrosis, changes in blood capillaries, tissue detachment, edema, degenerated connective tissues, and necrosis in large cerebellar neurons and ganglion cells. In the carp retina, there was evidence for necrosis, degeneration, vacuolation, and curvature in the inner layer. Here we provide evidence that exposure to plastic particles can be associated with neurotoxicity in common carp.